"Lussa Lalang Tinro": Raising Social and Environmental Accounting Responsibility through Film Analysis - Wa Ode Rayyani; Darwis Said; Nadhirah Nagu (International Journal of Religious and Cultural Studies, 2023)
This research aims to analyze the narrative elements in the film "Lussa Lalang Tinro" such as exposition, conflict, climax, and resolution, to understand how these elements interact and influence the audience's experience. The research adopts a qualitative approach and utilizes narrative analysis as the method. The film contributes to building awareness and understanding of social and environmental accounting responsibility through its strong storytelling and depiction of relevant issues. It invites viewers to reflect on the importance of considering social and environmental impacts in business and accounting practices. This research contributes by integrating film studies and social and environmental accounting, exploring a film that has received limited research attention, and providing fresh insights into how films can reflect and raise awareness of social and environmental accounting responsibility